The relationship between residual limb health, motion within the socket, and prosthetic suspension. Issue 4 (20th November 2022) - Baumann, Molly; Price, Ciera; Brousseau, Lauren; Loftsgaarden, Megan; Powell, Jordan; Sanders, Joan; Childers, W. Lee
Abstract: Residual limb health is critical for continued prosthesis use; however, many prosthesis users experience skin‐related breakdown. The interface between the residual limb and the prosthetic socket sets the local mechanical environment and plays a role in skin stresses. Motion of the residual limb in the socket adds additional mechanical strain on the limb. This article explores the relationship between motion of the limb in the socket and residual limb health. We evaluated current methods for assessing residual limb health and motion of the residual limb in the socket and compared these evaluations across different prosthetic suspension systems. While few direct studies comparing residual limb health and motion exist, it has been shown that elevated vacuum suspension systems result in both improved residual limb health compared to passive suction and pin‐lock systems and decreased motion compared to passive suction, pin‐lock, knee sleeve, and anatomical suspension systems. While motion and health have not been directly linked, elevated vacuum suspension may demonstrate a relationship that reduced motion of the residual limb in the socket improves residual limb health. Further evaluation in this area is necessary to more completely and directly understand the relationship between residual limb motion and residual limb health.